Microbial Control of Structural Insect Pests - Pereira, R. M.; Oi, D. H.; Baggio, M. V. [UNESP]; Koehler, P. G. (Elsevier, 2016)
Various reasons have prevented the microbial control of structural pests from reaching the commercial development and practical use achieved with agricultural pests. Microbial products have not been very successful on the market for the control of cockroaches throughout the world. The control of ants has focused on classical biological control agents used outdoors. Structural termite control has benefited little from work in agricultural systems, and doubts persist as to whether microbial control in structures can be successful. The recent resurgence of bed bugs has sparked an interest in the microbial control of these insects, but no commercial products are yet available. Without significant progress in the microbial control of the major structural pests, it is very unlikely that entomopathogens will become commercially available for the control of other structural pests. Due to the difficulties in fitting microbial products into structural pest management, monetary and time investments into the search and implementation of microbial control may lead to practical applications.
Keywords: Ants; Bed bugs; Cockroaches; Insect pathology; Microbial control; Structural pests; Termites